2014
DOI: 10.1302/0301-620x.96b4.32118
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, controlled trial of circumpatellar electrocautery in total knee replacement without patellar resurfacing

Abstract: In the absence of patellar resurfacing, we have previously shown that the use of electrocautery around the margin of the patella improved the one-year clinical outcome of total knee replacement (TKR). In this prospective randomised study we compared the mean 3.7 year (1.1 to 4.2) clinical outcomes of 300 TKRs performed with and without electrocautery of the patellar rim: this is an update of a previous report. The overall prevalence of anterior knee pain was 32% (95% confidence intervals [CI] 26 to 39), and 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(95 citation statements)
references
References 22 publications
3
92
0
Order By: Relevance
“…The literature mostly reports on surgery-related factors after TKA. The application of circumpatellar electrocautery does not lessen the incidence of AKP [30, 31]. Resurfacing the patella also remains controversial [3234].…”
Section: Introductionmentioning
confidence: 99%
“…The literature mostly reports on surgery-related factors after TKA. The application of circumpatellar electrocautery does not lessen the incidence of AKP [30, 31]. Resurfacing the patella also remains controversial [3234].…”
Section: Introductionmentioning
confidence: 99%
“…Search strategy and results are summarized in the Figure. A total of 52 titles were reviewed, of which 16 studies underwent a full-text review, of which 15 studies fulfilled the inclusion criteria and were included in the current review. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Summary data and quality of the included studies according to GRADE are reported in Table 1. Of the 15 included studies, 2 randomized, controlled trials (RCTs) were identified, 18,21 although the outcomes of secondary patellar resurfacing were not the focus of these RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the 15 studies reported outcomes only in terms of pain relief, without stating whether patients were satisfied. 14,20,21 Functional Scores Eight of the 15 studies reported knee specific scores (American Knee Society knee and function scores, Oxford Knee Score), 9,11,12,[15][16][17][18]23 and 2 studies reported patellar scores ( Table 1). 13,16 A statistically significant improvement in knee scores was noted in all studies.…”
Section: Very Lowmentioning
confidence: 99%
“…A randomized controlled trial study demonstrated that no benefi t was shown of TKR with patellar resurfacing over that without resurfacing with any of the measured outcomes [6]. Metaanalysis and systemic review studies were shown that there was no difference between the resurfacing and non-resurfacing group in terms of AKP but the rate of reoperation due to patella-femoral complication was signifi cantly increase in nonresurfacing patella [6][7][8][9]. The author compared the thickness reduction patella to the non-replacement patella because both technique were no prosthesis replacement and the incidence of AKP was not different between the replacement and non-replacement patella.…”
Section: Discussionmentioning
confidence: 99%